Proceedings of the 2000 Workshop on Computer Architecture Education - WCAE '00 2000
DOI: 10.1145/1275240.1275259
|View full text |Cite
|
Sign up to set email alerts
|

Virtual machines as an aid in teaching computer concepts

Abstract: A debugger containing a set of virtual assemblers and a virtual machine are used as teaching tools in order to teach students differences and similarities between architectural styles of computer processors. Programs written by the students in the virtual assemblers are compiled and executed in this environment so that the students can follow the execution of the programs step by step or at full speed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Some of these difficulties have been identified, and remedies suggested [1,5,7] According to our experience, we can highlight some of the problems faced by our students:…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Some of these difficulties have been identified, and remedies suggested [1,5,7] According to our experience, we can highlight some of the problems faced by our students:…”
Section: Introductionmentioning
confidence: 91%
“…We have searched the literature to try to locate a suitable system that meets all our objectives, but found that while some of the systems [3,4,8] and simulators [1,2,5] did cover our objectives severally no system could be found to cover all in our objectives.…”
Section: Copyright Held By Authormentioning
confidence: 99%
“…The first and second assignments were to write assembly language for a number of virtual machines [10,11,12] and to implement one of the virtual machines in any computer language, respectively.…”
Section: A Backgroundmentioning
confidence: 99%
“…One of the very nice features of DARK is that it offers four simple processor architectures in the same user interface. The architectures are stack machine, load-store machine, memorymemory machine and index-machine − all with their own simple and well documented instruction set [9].…”
Section: Dark Assemblermentioning
confidence: 99%